Legal-linguistic Analysis of EU Law and its Transpositions: a Useful Approach to Explore Harmonisation Problems? - Ruiz Cortés, Elena (Escuela de Administración Pública de Cataluña (EAPC), 2020)
The fact that the application of EU law leads to uneven practices across the Member States gives rise to heated debates in the literature. Research tends to focus on how the constraints of the EU law-making process contribute to threatening harmonisation in practice; however, the constraints of the transposition process are often overlooked. To bridge this gap, here we will explore both the supranational and national factors that may threaten harmonisation, using a legal-linguistic approach that will reveal the overlap between the legal and linguistic meanings in EU law. In particular, drawing on Robertson’s notions of “horizontal and vertical viewpoints” (Robertson, 2012a), we will perform a horizontal legallinguistic analysis of Article 3(2) of the Spanish and English versions of Directive 2004/38/EC on freedom of movement and residence, and a vertical legal-linguistic analysis of said Article in both language versions and its transposition in Spain and in the UK. Our results suggest that, in our case-study, both EU law-making and transposition-related factors may influence EU harmonisation problems in practice; factors such as EU strategic ambiguity or indeterminacy, political negotiations and supranational and national drafting decisions.
Anàlisi jurídica i lingüística del dret de la UE i de les seves transposicions: un enfocament útil per explorar problemes d’harmonització?
Keywords: Derecho comunitario; Harmonisation; Legal-linguistic horizontal and vertical analysis; Directive 2004/38/EC; Transposition; EU law-making